Pemanfaatan Fasilitas IT untuk Jaringan Pencahayaan LED di Smartroom - Mauludi Manfaluthy; Sinka Wilyanti (Universitas Syiah Kuala, 2019)
In this research, proposed lighting in smartroom with PoE technology (Power over Ethernet). IT facility is PoE Switch, Ethernet Cable and LAN network. Smartroom in this study is defined as meeting room in a high rise building that has LAN network. This research is motivated by many lighting lamps that use AC power, when the future use of AC source will be reduced, even with PoE switch voltage source still use AC, but can eliminate the pitch of light that still uses conventional AC. Building infrastructure systems tend to be developed towards IP protocols. An area where the electrical area becomes fully integrated into the IP network. This is made possible through the use of LED with low voltage and low current. However, in order to utilize the technical and economic advantages offered by LED Lighting Solutions, the addition of light sensor and motion as a switch will make it more complete. The results of the study obtained a cheaper cost than the use without PoE.